(untitled) (Proceedings of Faculty of Civil Engineering, 2025)
In this paper, newly developed quadrilateral finite elements of arbitrary order are presented for the linear vibration analysis of a 2D micropolar continuum. For the displacement field interpolation, two types of interpolation functions based on the fixed-pole concept are considered: the original and the enhanced (linked) interpolation. The developed finite elements with 4 and 9 nodes were subsequently employed to discretise several geometrical domains. Their convergence curves for the first two natural frequencies of the selected numerical examples are critically assessed against the results obtained using standard Lagrange interpolation.